2017
DOI: 10.1186/s13104-017-2547-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, speciation and antifungal susceptibility testing of Candida isolates from various clinical specimens at a tertiary care hospital, Nepal

Abstract: Background Candida species are responsible for various clinical infections ranging from mucocutaneous infection to life threatening invasive diseases along with increased resistance to antifungal drugs has made a serious concern. Resistance to antifungal agents has increased during the last decade. Thus, identification of Candida up to species level and its antifungal susceptibility testing has a paramount significance in the management of Candidal infections. The aim of the study was to speciate Candida speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
29
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 21 publications
12
29
4
1
Order By: Relevance
“…The commonest sample received were sputum (45%) and urine (33.5%) followed by other less common samples like pus (12%), vaginal swabs (5%), endotracheal secretion (1.5%), blood (1.5%) and tissue (1.5%). This was in accordance with other studies [2,6,[8][9][10]. The commonest isolate was C. albicans (58%) followed by C. tropicalis (20%), C. glabrata (10%), C. parapsilosis (9%) and C. krusei (3%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The commonest sample received were sputum (45%) and urine (33.5%) followed by other less common samples like pus (12%), vaginal swabs (5%), endotracheal secretion (1.5%), blood (1.5%) and tissue (1.5%). This was in accordance with other studies [2,6,[8][9][10]. The commonest isolate was C. albicans (58%) followed by C. tropicalis (20%), C. glabrata (10%), C. parapsilosis (9%) and C. krusei (3%).…”
Section: Discussionsupporting
confidence: 92%
“…Overall also, C. albicans (58%) pre-dominated as compared to NAC (42%). This was also observed in separate studies by Khadka et al and Khan et al [10,11]. This shows that NAC infections are also gaining importance as is also documented in another study by Bajwa and Kulshreshtha which showed that NAC rates in India range from 52% to 96% [12].…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings were found in a study where Candida species were found to be more susceptible to clotrimazole (82%) followed by miconazole (44%) respectively whereas 20% of total isolates were found to be resistant to fluconazole by disc diffusion method. 21 In previous studies the Candia spp was sensitive to antifungal agents. In Jordan, Al-Abeid et al (2004) showed that all tested Candida were susceptible to nystatin, miconazole, ketoconazole and fluconazole.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results for fluconazole and voriconazole sensitivity have also been obtained by Padawer D et al from Israel, Alkilani AA et al from Egypt and Khadke S et al from Nepal. [17][18][19] Two strains out of 113 (1.8%) isolated Candida were found as Susceptible dose dependant (S-DD). All the fluconazole resistant and S-DD isolates were further confirmed by E-test in our study, and it was found that both S-DD isolates proved to be resistant with MIC values >64.…”
Section: Resultsmentioning
confidence: 99%